2013
DOI: 10.1103/physrevlett.111.050601
|View full text |Cite
|
Sign up to set email alerts
|

Carnot Cycle at Finite Power: Attainability of Maximal Efficiency

Abstract: We want to understand whether and to which extent the maximal (Carnot) efficiency for heat engines can be reached at a finite power. To this end we generalize the Carnot cycle so that it is not restricted to slow processes. We show that for realistic (i.e. not purposefully-designed) enginebath interactions, the work-optimal engine performing the generalized cycle close to the maximal efficiency has a long cycle time and hence vanishing power. This aspect is shown to relate to the theory of computational comple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
175
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(181 citation statements)
references
References 21 publications
4
175
0
2
Order By: Relevance
“…They showed that, provided the critical exponents of the transition fulfill a suitable condition, then at the thermodynamic limit N → ∞ one can approach the Carnot efficiency, (η − η C ) ∼ N −a → 0 (with a > 0), while keeping the "power per resource" fixed, namely the power P ∼ N. It should be stressed that this means that the engine cannot achieve Carnot efficiency at finite power for any finite N, but it can do so in the limit N → ∞. A similar result was obtained by Allahverdyan et al [298] when considering a generalized Carnot cycle (i.e., not restricted to quasi-static processes), the working substance in contact with the thermal baths being a quantum system of size N. In that paper, it was shown that it is possible to obtain η → η C for N → ∞, at finite output power.…”
Section: Thermoelectricity and Electronic Phase Transitionssupporting
confidence: 48%
“…They showed that, provided the critical exponents of the transition fulfill a suitable condition, then at the thermodynamic limit N → ∞ one can approach the Carnot efficiency, (η − η C ) ∼ N −a → 0 (with a > 0), while keeping the "power per resource" fixed, namely the power P ∼ N. It should be stressed that this means that the engine cannot achieve Carnot efficiency at finite power for any finite N, but it can do so in the limit N → ∞. A similar result was obtained by Allahverdyan et al [298] when considering a generalized Carnot cycle (i.e., not restricted to quasi-static processes), the working substance in contact with the thermal baths being a quantum system of size N. In that paper, it was shown that it is possible to obtain η → η C for N → ∞, at finite output power.…”
Section: Thermoelectricity and Electronic Phase Transitionssupporting
confidence: 48%
“…Fig. 1), a result consistent with predictions for two-level systems [40] and Carnot heat engines [41]. W out increases with T 2 up to almost 3000 K. At 300 K for η max = 65.4% it is W out → 0.…”
Section: Otto Cyclesupporting
confidence: 88%
“…Among different optimization regimes, the efficiency at maximum power η maxP has been playing an important role for studies of traditional [11,32,33,[35][36][37][38][39][40][41], stochastic [31,[42][43][44][45][46][47][48], and quantum [49][50][51][52][53][54][55] HE. The maximum power and the efficiency at the maximum power η maxP of the present model, which were studied in Ref.…”
Section: A Optimized Regimes: Hementioning
confidence: 99%